Oil Spinner Machine to Improve the Quality of UMKM Chips Products in the Community of Food and Beverage Processed Association (IMO) of Sumatera Utara - Nasution, Dian Morfi; Bukit, Ferry Rahmat A.; Hasugian, Ivo Andika; Hasibuan, Novrida Harpah (Talenta Publisher, 2021)
Home industry is now increasingly in demand by the community as a form of